LOCAL FISH-BASED FOOD INTERVENTION FOR STUNTING PREVENTION IN INDONESIA: INTEGRATING EMPIRICAL EVIDENCE FROM VARIOUS REGIONS - Putra, Nico Syah; Zahirah , Nyayu Nabila; Putri, Delsi Diana; Awalina, Izza (SciencePlus, 2025)
Stunting is a chronic nutritional problem that remains a serious challenge to human resource development in Indonesia. This condition not only reduces children's linear growth but also has implications for brain development, endurance, and productivity in adulthood. One innovative strategy currently receiving attention is local food-based nutritional interventions, particularly fish as a source of animal protein that is cheap, easily accessible, and has high nutritional value. This article aims to synthesize various research results and community service activities from various regions in Indonesia regarding the use of local fish-based foods as an effort to prevent stunting in toddlers, while also assessing their effectiveness and implementation challenges. This study uses a systematic narrative review approach to ten national and local scientific publications (2019–2024) involving intervention activities, nutrition counseling, and local fish product development in South Sumatra, Central Kalimantan, West Aceh, Tanah Datar, and several other regions. Data are analyzed narratively based on the following categories: (1) form of intervention, (2) impact on child nutritional status, and (3) challenges and supporting factors for implementation. The use of local fish such as snakehead, bilih, patin, and catfish has shown an increase in animal protein consumption and a reduced risk of stunting. Interventions based on processed fish such as shredded fish, flour, nuggets, and fish powder improve the quality of complementary feeding (MP-ASI) and are well-received by the community. Nutrition education at the family level contributes to changes in consumption behavior. Key barriers include limited seasonal fish supplies and negative perceptions of the fishy aroma. Local fish- based food interventions have proven effective in improving children's nutritional status and families' nutritional knowledge. Cross-sectoral synergy between the government, academics, and the community is needed to strengthen local fish-based food security to accelerate stunting reduction